Maternal health in underserved tribal India - Amit Sengupta (Sexual and Reproductive Health Matter, 2019)
The paper brings the experience of implementing a behaviour change intervention to improve the use of maternity services in a rural tribal area in India in a population of 80,000 over five years between 2012 and 2017.
Keywords: Maternal health; Tribe; Access